Study on the interaction mechanism between slags and alkali silicate activators: A hydration kinetics approach. (30th July 2020) - Jin, Yu; Feng, Weipeng; Zheng, Dapeng; Dong, Zhijun; Cui, Hongzhi; Li, Mingyu; Sang, Guochen; Tang, Waiching
Highlights: Mixing sequence would greatly change the hydration kinetics of AAS. Dynamic equilibrium of silicate species would determine the hydration kinetics of AAS. Pseudo depolymerization degree can be used to predict the hydration kinetics of AAS. Abstract: In this study, the interaction mechanism between two types of blast furnace slags (named S1 and S2) with distinct chemical compositions and activators with various alkali and silicate concentrations were investigated. Based on the calorimetric results, it was found that the mixing sequence of alkali silicate solutions greatly changed the hydration kinetics of the alkali-activated slags (AAS), which indicates highly dynamic silicate structures in the activator. Although S1 with a higher specific surface area and basicity was less reactive than S2 in the presence of silicate anions, the influence of silicate anions on the hydration kinetics of alkali activated S1 and S2 was divergent. To solve the issues, NBO/T (the number of Non-Bridging-Oxygen per SiO4 Tetrahedral unit) ratio for the depolymerization degree of glass structure was innovatively introduced into AAS study by taking both precursor and alkali activator into consideration. The results show NBO/T has a strong capacity to predict hydration kinetics and compressive strength of AAS at early age. However, a dynamic equilibrium of the silicate species between the slag and water glass determined the hydration kinetics of the water glass-activated slag. This study provides a worthwhile exploration direction for clarifying the AAS hydration kinetics based on combination of quantitative glass structure index and isothermal calorimetrical analysis.